A Physician’s Guide to Recommending Yoga - Smith, Sarah (Am J Lifestyle Med, 2018)
The popularity of yoga in the United States and across the globe has been steadily increasing over the past several decades. The interest in yoga as a therapeutic lifestyle tool has also grown within the medical community during this time. However, the wide range of styles available to the public can make it difficult for patients and physicians alike to choose the one that will offer the most benefit. This guide was created to assist physicians in making informed recommendations for patients practicing yoga in the community. When the most suitable style is selected, yoga can be an extremely useful lifestyle tool for patients seeking to improve fitness and develop a mindfulness-based practice.